The smarter bomb women and children as suicide bombers - Berko, Anat (Rowman & Littlefield, 2012)
This book offers a rare glimpse into the motivations of suicide bombers, especially women and children, and those who recruit and dispatch them. Able to win the trust of imprisoned bombers, Anat Berko records their searing personal stories, offering a candid portrayal for all those wanting to understand and communicate with terrorists.